EVALUASI DAN PROGRAM PEMELIHARAAN JEMBATAN DENGAN METODE BRIDGE MANAGEMENT SYSTEM (BMS) Studi Kasus Lima Jembatan Jalan Nasional Provinsi D.I Yogyakarta - , LALU YUDI KUSUMA WIJAYA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The bridge is a structure that crosses a river, chasm / gap, traffic intersections, bays and other obstacles which aimed to pass traffic from one place to another place,. The success of the role and function of the bridge depend on the management, the government throught Ditjen Bina Marga Kementerian Pekerjaan Umum since 1993 has been developing a bridge management system that is known as Sistem Manajemen Jembatan (SMJ) or Bridge Management System (BMS). The system allows to make a plan systematically and to provide a uniform procedure for bridge activities in national and provincial level. The research was conducted on five locations of bridge on national street of Yogyakarta province that were Krasak Lama Bridge, Gamping Bridge, Gajah Wong Bridge, Winongo Bridge and Bedog Bridge, bridge condition assessment was done visually to find out the overall bridge existing accoarding to the Bridge Management System (BMS) standard and by the help of information system of Bridge Management System (SIM-IBMS) which was computer based. The result of condition value for the fifth of bridge according to Bridge Management System (BMS) was, on the Krasak Lama Bridge the condition value was 2, the Gamping Bridge which consists of the Gamping Lama Bridge and Gamping Baru Bridge the value of conditions were 2, the Gajah Wong Bridge which consists of Gajah Wong A,B and C the value of each conditions were 2, 2 and 1, the Winongo Bridge which consists of Winongo A, B and C the value of conditions of each conditions were 1, 2 and 0, the Bedog Bridge which consists of Bedog A, B and C the value of conditions in a row were 1, 2 and 1. The proposed treatment based on technical screening in a form of sub-element rehabilitation used for the Krasak Lama Bridge, rehabilitation of superstructuture used for the Gamping Lama Bridge and rehabilitation of the riverbed controller used for the Gamping Baru Bridge. To Gajah Wong Bridge consecutively was rehabilitation of sub-element used for Gajah Wong A Bridge, rehabilitation water ways areas and rehabilitation of riverbed controllerused for Gajah Wong B and rehabilitation of water way areas used for Gajah Wong C Bridge, while for the Winongo A Bridge, Winongo B Bridge , Bedog A Bridge, Bedog B Bridge and Bedog C Bridge proposed rehabilitation was in form of rehabilitation of sub-element and for Winongo C the proposed rehabilitation was a routine inspection. The cost of repairing the damage to the fifth bridge in a row were RP 167.268.000 for Krasak Lama Bridge, RP 67.970.000 for Gamping Bridge, Rp 72.788.000 for Gajah Wong bridge, Rp 41.759.000 for winongo Bridge and last Rp 19.094.000 for Bedog Bridge.